PROSES PENGURUSAN SERTIFIKASI TANAH WAKAF DI KABUPATEN SUKOHARJO DAN KABUPATEN KARANGANYAR - Moh Khoirul Anam Anam; Nurul Fitroh (EL-ADABI : Jurnal Studi Islam, 2025)
Waqf during the time of the Prophet and the Caliph was able to solve social problems such as poverty, In this modern era, the management of waqf that occurs among the community has not been fully carried out in an orderly and effective manner. Waqf property in the form of land that is not properly maintained, or even changed hands to other parties illegally. Problems in the management of waqf land certificates are caused by a combination of various factors, such as low public understanding, bureaucratic complexity, legality issues, limited resources, and lack of synergy among related institutions.  This study aims to analyze these problems, by looking at the practice of waqf land certification services by the government through authorized agencies, whether in service practice there is good governance, which should be the solution to the current problem.  This study uses data collection with participatory observation, where the researcher is involved in the object being studied.  The results of the study explained that the process of managing waqf land certification in Karanganyar Regency, Central Java Province is very easy and fast, which is about 6 (six months) using the One-Stop Integrated Waqf Service System. This happens, of course, because of the cooperation and good communication between the Ministry of Religion and the Ministry of ATR/ BPN Karanagnyar Regency, Central Java Province. Meanwhile, the process of managing land certification in Sukoharjo Regency takes a very long time, namely 1 (one) year and 9 (nine) months.